2018
DOI: 10.1159/000496001
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analyses of Renal Ischaemia-Reperfusion Injury Models: Identification of Key Genes Involved in the Development of Kidney Disease

Abstract: Background/Aims: To develop a novel strategy for the treatment of kidney disease, we explored potential molecular targets involved in the development of renal ischaemia-reperfusion injury (IRI). Methods: The Gene expression profile data of GSE27274, including controls and rats subjected to renal IRI and reperfusion for 24 h (IR24) or 120 h (IR120), was obtained from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) were analysed using the limma package. Gene Ontology (GO) and pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…As shown in Figure 3C, the miR-142 expression levels were significantly reduced in HIRI group, compared with Sham group, however, this inhibitory effect was dramatically reversed by Sevo postconditioning. Previous studies have reported that miR-142 plays important roles in regulating I/R injury in other organs, such as kidney and heart (Zhu et al, 2018;; thus, we proposed that Sevo postconditioning may improve hepatic I/R injury by reverting I/R-induced downregulation of miR-142.…”
Section: Sevo Postconditioning Reverts I/r-induced Downregulation Of Mir-142mentioning
confidence: 86%
See 1 more Smart Citation
“…As shown in Figure 3C, the miR-142 expression levels were significantly reduced in HIRI group, compared with Sham group, however, this inhibitory effect was dramatically reversed by Sevo postconditioning. Previous studies have reported that miR-142 plays important roles in regulating I/R injury in other organs, such as kidney and heart (Zhu et al, 2018;; thus, we proposed that Sevo postconditioning may improve hepatic I/R injury by reverting I/R-induced downregulation of miR-142.…”
Section: Sevo Postconditioning Reverts I/r-induced Downregulation Of Mir-142mentioning
confidence: 86%
“…In this study, microarray screening revealed miR-142 was one of the major miRNAs that were upregulated in mice by Sevo treatment. Previous studies have demonstrated that miR-142 improved I/R injury in different organs including heart (Su et al, 2019) and kidney (Zhu et al, 2018); however, whether miR-142 is involved in the protective mechanisms of Sevo postconditioning in hepatic I/R injury remains unknown. In our findings, it was confirmed that the agomir-142 injection enhanced the protective effects when compared with Sevo, while the antagomir-142 injection suppressed the therapeutic effects of Sevo in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is a mitochondrial matrix enzyme with roles in choline degradation, one-carbon metabolism and electron transfer to the respiratory chain (Augustin et al, 2016). DMGDH is a key metabolic enzyme, linked to diabetes, kidney disease (Zhu et al, 2018;Magnusson et al, 2015), carcinoma and metastasis (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although various bioinformatics analyses of reperfusion in other organs and animals have been performed, a systematic and thorough analysis of cardiac IR in human hearts is still lacking (17,18). Therefore, in this study, a co-expression correlation network was constructed using the expression data from the gene expression omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%